The Determinant of Lung Function Disorders of The Textile Industry Spinning Section - Suryadi, Iwan; Nugraha, Aditama Putra; Fitriani, Nurlaila; Rachmawati, Siti (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Many factors affect lung function capacity in textile industry workers. This research aims to determine the factors that affect the vital role of pulmonary spinning workers in the textile industry. This research used an analytic observational research design with a cross-sectional approach. The sampling technique used total sampling and getting the sample was 96 people, and measurement of lung vital capacity used spirometry. The Low Volume Sampler was applied to measure dust concentration, and the questionnaire was used to assess the individual characteristics. Bivariate analysis of the variables is the working environment dust, exercise habits, smoking behavior, and gender are significant. The result of multivariate analysis of dust is the most affecting to the lung vital capacity. In conclusion, dust concentrations are classified above the Threshold Limit Value (TLV), so the company should control the source of dust exposure.